Qaḍāyā Muʾaddiyah ilā Iṣlāḥ al-Manhaj al-Taʿlīmī li al-Lughah al-ʿArabiyyah - Ahmad Fathoni (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2016)
Curriculum reform is one of the most essential issues in language education, as it serves as the foundation for all teaching and learning processes. Through curriculum development, educational objectives are established, instructional programs are designed, learning activities and teaching strategies are determined, targeted competencies are identified, and appropriate assessment methods are developed to support effective teaching and meaningful learning. This study discusses the reform of the Arabic language curriculum from both theoretical and practical perspectives in order to ensure that Arabic language education keeps pace with ongoing scientific and technological advancements. It aims to equip learners with linguistic competencies that can be effectively applied in various contexts of oral and written communication. The study focuses on reforming the curriculum for teaching Arabic as both a foreign language and the language of Islamic education. This topic is particularly important because curriculum reform constitutes the foundation for improving Arabic language education in Indonesia. The study emphasizes the necessity of conducting comprehensive curriculum evaluation before implementing any reform, taking into account national educational policies as well as political, social, and technological contexts. Ultimately, it argues that meaningful improvement in Arabic language education requires the development of an appropriate curriculum and language policy capable of addressing educational challenges and meeting contemporary learning needs.